Challenges in Teaching Tax Treaties - van Raad, Kees (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This contribution deals with the interaction between domestic tax law and tax treaties. It provides an illustration of this interaction on the basis of the notion ‘permanent establishment’. Further, it deals with the difference that may exist between tax treaty and domestic law definitions of individual income items. It concludes with an explanation of the issues that arise when divergent income definition rules of two treaties need to be applied simultaneously and how such application of treaty rules interacts with the application of domestic law.